2020
DOI: 10.3389/fendo.2020.00561
|View full text |Cite
|
Sign up to set email alerts
|

High-Intensity Interval Training Restores Glycolipid Metabolism and Mitochondrial Function in Skeletal Muscle of Mice With Type 2 Diabetes

Abstract: High-intensity interval training has been reported to lower fasting blood glucose and improve insulin resistance of type 2 diabetes without clear underlying mechanisms. The purpose of this study was to investigate the effect of high-intensity interval training on the glycolipid metabolism and mitochondrial dynamics in skeletal muscle of high-fat diet (HFD) and one-time 100 mg/kg streptozocin intraperitoneal injection-induced type 2 diabetes mellitus (T2DM) mice. Our results confirmed that high-intensity interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 75 publications
(90 reference statements)
4
14
0
Order By: Relevance
“…Our results indicate that both DHIIT training protocols reduced FBS levels to a similar extent, suggesting that either a 1 or 2 min of recovery time improved fasting blood glucose levels and reduced FBS levels in both groups to the same extent. These observations are consistent with previous findings that HIIT reduces hyperglycemia in diabetic patients (Little et al, 2011a;Alvarez et al, 2016) and rodents (Chavanelle et al, 2017;Zheng et al, 2020). Insulin-stimulated GLUT-4 translocation is disrupted in diabetes, and exercise training stimulates the translocation of GLUT-4 to the muscle cell membrane in diabetic patients (Kennedy et al, 1999;O'Gorman et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results indicate that both DHIIT training protocols reduced FBS levels to a similar extent, suggesting that either a 1 or 2 min of recovery time improved fasting blood glucose levels and reduced FBS levels in both groups to the same extent. These observations are consistent with previous findings that HIIT reduces hyperglycemia in diabetic patients (Little et al, 2011a;Alvarez et al, 2016) and rodents (Chavanelle et al, 2017;Zheng et al, 2020). Insulin-stimulated GLUT-4 translocation is disrupted in diabetes, and exercise training stimulates the translocation of GLUT-4 to the muscle cell membrane in diabetic patients (Kennedy et al, 1999;O'Gorman et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…We provide novel findings on the effects of two different HIIT protocols on the regulation of PGC-1α protein and gene expression in diabetic rats. The observed increases in the expression levels of PGC-1α protein produced by HIIT were supported by other studies in obese rats (Khalafi et al, 2020), diabetic mice (Zheng et al, 2020), and humans (Hood et al, 2011). Although the molecular mechanisms by which HIIT induces mitochondrial signaling pathways are unclear, there is some evidence that the intermittent effort and the reoccurrence of metabolic fluctuations in the skeletal muscle may play a role (Combes et al, 2015).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…It was followed in animal experiments that the improvement of BG and BI in T2D mice after 8-week HIIT accompanied by the increase of glycogen content in skeletal muscle ( 48 ). Some studies have shown that upregulation of GLUT4, increased aerobic enzyme activity, and mitochondrial biogenesis may be a potential mechanism of HIIT promoting glucose uptake and improving insulin sensitivity ( 17 , 50 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…The potent effect of exercise to increase GLUT4 expression not only enhances insulin action but facilitates muscle glycogen storage following exercise training. 65 The increase in energy demand brought about by exercise is also a potent stimulus to increase mitochondrial function and content. 66 Studies in both humans and rodents have found strong associations between the level of physical activity and changes in mitochondrial content and function.…”
Section: Exercisementioning
confidence: 99%